Gestures of love : romancing performance in classical Hollywood cinema - Rybin, Steven, 1979- (Albany : State University of New York Press, 2017)
Gestures of Love" considers the viewer's enchantment with charismatic actors in film as the starting point for closely analyzing the performance of love in movies. Written with a thoughtful adoration for the actors who move us, Steven Rybin examines several of cinema's most beloved on-screen movie couples, including Katharine Hepburn and Cary Grant, Myrna Loy and William Powell, Carole Lombard and John Barrymore, Gene Tierney and Dana Andrews, Lauren Bacall and Humphrey Bogart, and Rock Hudson and Dorothy Malone. Using the classical genres of screwball comedy, film noir, and the family melodrama as touchstones, Rybin places the depiction of romance in films into dialogue with the viewer's own emotional bond to the actors on the screen. In doing so, he offers rich new analyses of such classic films as Bringing Up Baby, The Thin Man, Twentieth Century, Laura, To Have and Have Not, Tea and Sympathy, Written on the Wind, and more.
Introduction: The actor's heartbeat -- Part one: Screwball love -- Love's final irony: John Barrymore and Carole Lombard in Twentieth century -- Wicked jaws, lanky brunettes: Myrna Loy and William Powell in The thin man and Libeled lady -- "You look so silly": Katharine Hepburn and Cary Grant in Sylvia Scarlett, Holiday, Bringing up baby, and The Philadelphia story -- Part two: noir amour -- Love's possession: Dana Andrews and Gene Tierney in Laura -- Wooing bogie, courting Bacall: Humphrey Bogart and Lauren Bacall in To have and have not, The big sleep, Dark passage, and Key Largo -- Part three: Love and melodrama -- Lipstick on a teacup: performance in Vincente Minnelli's The cobweb and Tea and sympathy -- Hudson, Bacall, Stack, Malone: love and gesture in Douglas Sirk's Written on the wind -- Coda: Modern love.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
eBooks on EBSCOhost
Keywords: Love in motion pictures; Motion pictures -- United States -- History -- 20th century; Motion pictures -- Production and direction -- United States -- History -- 20th century; Motion pictures -- California -- Los Angeles -- History -- 20th century; Motion picture acting; Amour au cinéma.; Cinéma -- États-Unis -- Histoire -- 20e siècle.; Cinéma -- Production et réalisation -- États-Unis -- Histoire -- 20e siècle.; Cinéma -- Californie -- Los Angeles -- Histoire -- 20e siècle.; Art de l'acteur au cinéma.; PERFORMING ARTS -- Reference; Love in motion pictures; Motion picture acting; Motion pictures; Motion pictures -- Production and direction; California -- Los Angeles; United States; 1900-1999; Electronic books; History